Non-CO2 emission from cropland based agricultural activities in India: A decomposition analysis and policy link. (10th July 2019) - Some, Shreya; Roy, Joyashree; Ghose, Arpita
Abstract: Cropland–based agricultural activities emit 34.13% of the total non-carbon dioxide emission in India as of 2007 and contribute 63% of the gross value added from agriculture as of 2014–15. It accounts for 24.17% of the India's total methane and 95.84% of the total nitrous oxide emission from agricultural sector. This article analyzes the change in non-carbon dioxide greenhouse gases emission overtime from India's cropland based agricultural activities for the period of 1980–81 to 2014–15 and uses Logarithmic Mean Divisia Index to identify the factors that are driving this emission change. Results show that during the study period methane emission from paddy cultivation declines at statistically insignificant rate of 200 tonnes per year whereas nitrous oxide emission from nitrogen-fertilizer use increases by approximately 358%, growing at a statistically significant rate of 5100 tonnes per year. Fertilizer intensity contributes 48% in the growth of non-carbon dioxide greenhouse gases emission from cropland based agricultural activities followed by affluence and population growth. On the contrary structural change of the economy with declining relative contribution of agriculture in national gross domestic product, improved productivity of fertilizer use, declining cultivated land per unit of agricultural output and declining emission intensity are helping to reduce emission. Empirical analysis clearly show link between fertilizer policy intervention and nitrous oxide emissions indicating role of policy as an important driver in managing non-carbon dioxide emission from India's cropland–based agricultural activities. Highlights: Methane emission from paddy fields in India declined marginally during 1980–2015. Years when yield from fertilizer use increased non-CO2 emission came down. Fertilizer policy led to unbalanced use of N-fertilizer increasing N2 O emission. Intensive agricultural practices in India are pulling down non-CO2 emission.